Key questions for conservation tenders as a means for delivering biodiversity benefits on private land. (28th May 2021) - Fitzsimons, James; Cooke, Benjamin
Summary: In 2021, as part of the Convention on Biological Diversity, the world's nations will meet to determine biodiversity targets for this decade, including area‐based protection targets. Conservation tenders (a form of market‐based instrument) have been used in several countries for the protection and restoration of biodiversity and ecosystem services​ within a defined area, mostly on private land. Conservation tenders are promoted as delivering cost‐effective and targeted investment/outcomes in the context of limited funding for conservation. Despite the significant investment in the approach, the resultant biodiversity conservation outcomes from these tenders have received relatively little research attention. Key questions on the efficacy of conservation tenders for achieving biodiversity conservation outcomes are discussed, to inform policy makers, programme managers and researchers. Questions include the following: (i) What are the conservation objectives that conservation tenders seek to address that other mechanisms cannot?, (ii) What have been the biodiversity outcomes realised as they relate to ecosystem/habitat representation or ecosystem services?, (iii) How do policy makers plan to realise biodiversity values beyond the term of the agreement given no publicly stated strategy on securing long‐term outcomes?, (iv) Is reporting of activities and results sufficient to judge changed biodiversity condition or delivery of expected outcomes at the end of the agreement, and are there efforts/plans/aims to follow up on outcomes post the agreement term?, (v) What proportion of successful tenderers have a protective conservation covenant in place prior to signing a tender or as a result of signing a tender agreement?, (vi) What do we know about the intentions and capacity of landholders beyond the term of the agreement and what has been the fate of agreements (and conservation outcomes) if they have changed hands during the course of the agreement?, (vii) Is the confidential nature of bidding in many conservation tenders missing the opportunity for collective or collaborative conservation efforts that can sustain learning and enthusiasm post‐tender?, and (viii) Is the information on ecological values (ecosystem type, quality, landscape context etc) presented or made available in a way to landholders that maximises likely bidding to ensure a large pool and thus programme efficiency?